Analisis Stilistika dan Fungsi Sosial Khutbah Jumat Sunan Giri dalam Konteks Penyebaran Islam di Nusantara: Stylistic Analysis and Social Function of Sunan Giri's Friday Sermon in the Context of the Spread of Islam in the Archipelago - Abshar, Ulil; Sa’diyah, Solikhatus; Muhtarom, Ahmad; Hidayatullah, Muhammad Fikri Al-Mujaki; Farihin, Zainul (Information Technology and Science(ITScience), 2025)
This study examines the Sunan Giri Friday Sermon (KKJSG) as one of the important religious texts from the early period of Islam in Java. As a preaching and educational text, KKJSG combines classical Arabic rhetoric with local cultural elements, thus becoming an important representation of the process of indigenization of Islam in the archipelago. The study uses a qualitative descriptive approach with stylistic and content analysis. The primary data consists of twelve sermons in KKJSG, which are analyzed based on their structure, language patterns, stylistic devices, and social functions. Data collection techniques include textual reading, identification of stylistic elements, and thematic categorization. The study shows that KKJSG has a standard sermon structure name, introduction, content, and conclusion that is consistent across all Hijri months. Dominant stylistic devices include saj’, jin?s, and iqtib?s, each serving to strengthen rhetorical power, add symbolic capital, and provide religious legitimacy. The combination of Arabic (70%) and Javanese (30%) and the agrarian-maritime metaphors demonstrates the process of cultural adaptation in Sunan Giri's preaching. Other findings indicate that the sermons function multidimensionally, namely as a means of preaching, Islamic boarding school education, and legitimizing political leadership. The results of this study confirm that the KKJSG is not merely a religious text, but also a medium for the formation of Javanese Islamic identity through a creative dialogue between global texts and local culture. Further research is recommended to conduct philological studies, comparisons of Nusantara preaching manuscripts, and technology-based linguistic analysis to enrich the understanding of the stylistics of Nusantara Islam.